Recent Advances in Transthyretin Evolution, Structure and Biological Functions - Richardson, Samantha J.; Cody, Vivian (Springer Berlin Heidelberg : Imprint: Springer, 2009)
There is a strong interest in transthyretin (TTR) in connection with protein evolution, medical and clinical research. Thus, this is an exciting time for experts in TTR research to come together to write a monograph covering both the basic and the clinical research into TTR. Transthyretin is a protein found in human blood and cerebrospinal fluid. It is directly involved in the transport of thyroid hormones, and indirectly in that of retinol. These hormones are essential for normal growth and development, particularly that of the brain. Spontaneous and inherited diseases affecting transthyretin result in amyloidosis. More than 80 point mutations in transthyretin lead to a variety of illnesses. Liver transplants are the most common treatment, although much research is also being carried out in drug therapies. The evolution of transthyretin has been extensively investigated - from humans to bacteria, invertebrate animals and plants. The structure of the protein has not changed, but its function has changed significantly. This is a most exciting example for the study of the evolution of protein structure-function relationships. This monograph will bring the reader up to date on the latest developments and discoveries.